Effect of Soaking and Concentration of Liquid Organic Fertilizer (POC) Cow Urine Against Early Grape Cuttings (Vitis Vinevera. L). - Yudha Dwi Hansah; Sri Purwanti; Nurul Huda (Agricultural Science, 2020)
use of vine stem cuttings seeds has the advantage of providing more number of seeds and later new plants which will have properties such as the parent, grapes are already known as one of the classy fruits in the world, both fresh consumed and processed products, processed grape products which is known as wine is able to penetrate the price of Rp5.7 billion per bottle is famously expensive in subtropical countries. This study aims to determine the duration of soaking and concentration of liquid organic fertilizer (POC) of cow urine on the initial growth of grape cuttings. The study was conducted in the Experimental Garden Faculty of Agriculture, Merdeka University, Surabaya Jl. Ketintang Madya VII / 2 Surabaya, with a height of ± 5 meters above sea level. This study uses a randomized block design (RBD) arranged according to factorial patterns with two (2) factors, namely factor I = duration of immersion consisting of 4 levels, including: L0 = 0 minutes (control), L1 = cuttings of grapes soaked for 15 minute, L2 = cuttings of grapes soaked for 30 minutes, L3 = cuttings of grapes soaked for 45 minutes, while factor II = concentration of organic ZPT consists of 3 levels, including P0: 0 ml / liter (water), P1: 10 ml cow urine per liter of water, P2: 20 ml cow urine per liter of water, P3: 30 ml cow urine per liter of water, P4: 40 ml cow urine per liter of water, based on the results of the study, conclusions can be drawn. There was a significant interaction at the F5% test level on the variables studied, namely the length of the vine cuttings at 42 days after planting and was best achieved by a combination of P3L2 treatment compared to other treatments, although it was not significantly different from the combination of P2L3 and P4L2 treatments. significant from both the POC concentration factor and the immersion length factor under study, mainly in the shoot length variable at 42 days after planting. Statistically, a better value for all of these variables is achieved by the P3 treatment that is 30% ml / liter of water and the L2 treatment that is 30 minutes.